CPUE TRENDS OF THE INDONESIA’S TUNA LONGLINE FISHERY: LESSONS LEARNED FROM A TRIAL OBSERVER PROGRAM - Lilis Sadiyah; Natalie Dowling; Budi Iskandar Prisantoso; Retno Andamari; Craig Proctor (Research Center for Fisheries, 2014)
In an effort to address a shortage of reliable CPUE information, and as a preliminary step to a broader observer program, Indonesia established a Trial Observer Program (TOP) for the industrial tuna long line fishery based at Benoa Fishing Port, Bali, in mid 2005. The objectives of this paper are i) to describe spatial and temporal catch and effort trends from the Indonesian Indian Ocean industrial tuna long line fishery based at Benoa Fishing Port, and ii) to provide an understanding of the fishing strategies used by different companies and of the environmental conditions that may influence catch trends. The observed effort covered areas both north and south of 20°S, with a concentration within 10°-20°S; 105°-120°E which overlaps with the only known spawning grounds of southern bluefin tuna (SBT). This data set showed that SBT comprised the lowest catch proportion, relative to the other three tuna species caught, bigeye tuna (BET), yellowfin tuna (YFT) and albacore (ALB). BET and ALB had been suggested as the main target species for the fishery, but this varied by region. The TOP data set suggests that different tuna fishing companies targeted different species and used different fishing practices, including differences in bait used, areas fished, start time of setting, and the number of hooks between floats (HBF). It is a priority to improve the spatial and temporal coverage of the observer program before the data can be considered to be representative of the fleet, particularly given the high degree of variability in fishing practices between companies.